On the incompatibility of object fronting and progressive aspect in Yucatec Maya - Uth, Melanie; Gutiérrez-Bravo, Rodrigo; Fliessbach, Jan (Frontiers in Language Sciences, 2024)
In this paper, we present data from an elicitation study and a corpus study that support the observation, mentioned but not investigated in Bohnemeyer (2002, p. 265), that the Yucatec Maya progressive aspect morpheme táan is replaced by the imperfective morpheme k in sentences with fronted objects. Considering that the Yucatec Mayan habitual morpheme k “carries aspectual information only in contrast with more specific auxiliaries” (Lehmann 2017, p. 203), we suggest a semantic-pragmatic explanation based on the following literature. In terms of Comrie’s (1976) subdivisions of imperfectivity, we consider táan as a specific encoder of the progressive, to the exclusion of a habitual reading. Following Ferreira (2016), we take a progressive reading to be derived from an imperfectivity operator in combination with a singular operator. Based on Rooth (1992), we propose that this singular operator implicates the negation of event plurality, leading to an exhaustive interpretation which ranks below corrective focus on the contrastive focus scale in Cruschina (2021, p. 2). This means that the use of the specific and marked form, táan, as opposed to the more general k, in a Yucatec sentence with corrective object fronting would therefore trigger two contrastive foci, possibly of different strengths, which is an unlikely and probably dispreferred “strategy of inquiry” (Beaver, Roberts, Simons, Tonhauser 2017: 267-269). For future experimental investigations, our account predicts that a combination of focus fronting and táan should receive similarly low acceptability ratings as other sentences containing two instances of contrastive focalization.